A new class of nanocomposites of Zn–Al–Bi layered double oxides: large reversible capacity and better cycle performance for alkaline secondary batteries. Issue 95 (28th September 2016) - Long, Jun; Yang, Zhanhong; Zeng, Xiao; Huang, Jianhang
Abstract : Zn–Al–Bi layered double oxide (Zn–Al–Bi-LDO) nanocomposites with a bilayer structure were prepared by calcining Zn–Al–Bi layered double hydroxides (Zn–Al–Bi LDHs) in an air atmosphere at 600 °C for 6 h. Abstract : Zn–Al–Bi layered double oxide (Zn–Al–Bi-LDO) nanocomposites with a bilayer structure were prepared by calcining Zn–Al–Bi layered double hydroxides (Zn–Al–Bi LDHs) in an air atmosphere at 600 °C for 6 h. The prepared Zn–Al–Bi-LDO nanocomposite products and the Zn–Al–Bi LDH-based materials are characterized by energy dispersive spectrometry (EDS), X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The characterization results demonstrate that the well-crystallized Zn–Al–Bi-LDOs are completely synthesized, retaining a hexagonal sheet structure. Herein, we intensively study the electrochemical performances of Zn–Al–Bi-LDO and ZnO electrodes using galvanostatic charge–discharge measurements, cyclic voltammograms (CV), and Tafel polarization for a Ni/Zn secondary battery. The as-prepared Zn–Al–Bi-LDO (Zn/Al/Bi = 3 : 0.8 : 0.2) electrode with special characteristics exhibits an outstanding cycle performance (533 mA h g −1 after 800 cycles at 1C) and a better rate capability (512 mA h g −1 at 5C).